Pengaruh Lingkungan Kerja Dan Komitmen Organisasional Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Bima - Muhammad Naufal Azmin; Ikbal Irawan; Karti Aprianti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine the influence of the work environment and organizational commitment on employee performance at the Public Works and Spatial Planning Agency of Bima Regency. The study employs associative research with a quantitative approach. The population consists of all 201 employees at the agency, comprising 90 Civil Servants (PNS), 37 Government Employees with Work Agreements (PPPK), and 74 honorary staff members; a sample of 90 individuals was selected. The results indicate that the work environment has a positive and significant influence on employee performance at the Public Works and Spatial Planning Agency of Bima Regency. Organizational commitment also has a positive and significant influence on employee performance at the agency. Furthermore, the work environment and organizational commitment simultaneously exert a significant influence on employee performance at the Public Works and Spatial Planning Agency of Bima Regency.